2018
DOI: 10.1371/journal.pgen.1007628
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ACD6 dependent hyperimmunity by natural alleles of an Arabidopsis thaliana NLR resistance gene

Abstract: Plants defend themselves against pathogens by activating an array of immune responses. Unfortunately, immunity programs may also cause unintended collateral damage to the plant itself. The quantitative disease resistance gene ACCELERATED CELL DEATH 6 (ACD6) serves to balance growth and pathogen resistance in natural populations of Arabidopsis thaliana. An autoimmune allele, ACD6-Est, which strongly reduces growth under specific laboratory conditions, is found in over 10% of wild strains. There is, however, ext… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 97 publications
0
14
0
Order By: Relevance
“…natural variation in the immune gene ACCELERATED CELL DEATH 6 (ACD6) is caused by a rare allele causing an extreme lesion phenotype. It is not yet clear what selective pressures influence ACD6 genetic variation (Todesco et al, 2010;Zhu et al, 2018). The contrast where Aliphatic GSL loci have high levels of allelic heterogeneity for independent and recurrent LOF and GOF events while other resistance genes have more stable biallelic variation suggests that there are different selective regimes influencing these loci.…”
Section: Discussionmentioning
confidence: 99%
“…natural variation in the immune gene ACCELERATED CELL DEATH 6 (ACD6) is caused by a rare allele causing an extreme lesion phenotype. It is not yet clear what selective pressures influence ACD6 genetic variation (Todesco et al, 2010;Zhu et al, 2018). The contrast where Aliphatic GSL loci have high levels of allelic heterogeneity for independent and recurrent LOF and GOF events while other resistance genes have more stable biallelic variation suggests that there are different selective regimes influencing these loci.…”
Section: Discussionmentioning
confidence: 99%
“…Allelic interactions at the ACD6 (ACCELERATED CELL DEATH 6) locus in A. thaliana lead to hybrid necrosis and the enhanced expression of defense genes (Świadek et al 2017). In fact, ACD6 acts as a quantitative resistance gene that balances growth and pathogen resistance in natural populations of A. thaliana, and it has been shown that deleterious autoimmune ACD6 alleles are modulated by natural variants of SNC1 (Zhu et al 2018).…”
Section: Hr Cell Death As a Consequence Of Autoimmunitymentioning
confidence: 99%
“…Epistatic interactions have been well-documented as underlying autoimmune responses and pathogen resistance in Arabidopsis (Bomblies et al, 2007;Alcázar et al, 2009;Chae et al, 2014;Zhu et al, 2018). Genetic analyses in these studies have implicated certain gene clusters or individual loci as important, but the biochemical or physical mechanism underlying the resultant phenotypes (e.g.…”
Section: Potential Epistatic Selection Of Gi CVI and Ztl Cvimentioning
confidence: 99%